Réponse associative à l’inégal accès au traitement Hydréa chez les enfants drépanocytaires de forme sévère en Côte d’Ivoire - Tenguel Sosthène N’GUESSAN (Revue Hybrides)
A hereditary hemoglobin disease, sickle cell disease is a public health problem in Côte d’Ivoire. Sickle cell disease affects 16.3% of children under the age of four, 65.5% of school-aged children between 5 and 14 and 18.2% of those over the age of 15. Despite this gloomy epidemiological context and state action, access to effective treatment for disease management is uneven for sickle cell patients. Faced with this challenge of health and social significance, the Lya Foundation has undertaken the implementation of a hydroprophylaxis of about a hundred sickle cell children of severe form. This article analyses the Lya Foundation’s contribution to access to Hydraea treatment in children with severe sickle cell disease. Carried out at the clinical hematology department of the Yopougon Hospital and University Center, this study combined quantitative and qualitative approaches. Descriptive and content analyses made it possible to give meaning to the data and corpus constituted. The study reveals that treatment with hydraea is an opportunity to improve the health of the sickle cell child. Perceived as an optimal treatment for the management of sickle cell disease, water treatment reduces its free access to poor populations, improves the emotional state of the sickle cell child and promotes an emotional renewal in children. Beyond the medical aspect, the action of the foundation strengthens the sociability of the child, arouses a renewed attention for his school curriculum, one of the consequences of which is the academic performance. The pilot experience of access to hydrea remains an opportunity to democratize access to said therapy. This action deserves to be supported by the State in view of the cost of therapy to which therapeutic education should be added for both sickle cell children and parents/carers and teachers/trainers.